EFFORTS TO IMPROVE THE PREVENTION OF FISHERY CRIME ACCORDING TO ISLAMIC LAW - Riza, Faisal; Amami, Ihsanil (Proceeding International Seminar of Islamic Studies, 2023)
Potential fisheries resources are a blessing from the one and only God. In order for these fish resources to remain sustainable and maintained, the prevention aspect is very important to be developed and implemented by everyone, especially fishermen. Law Number 45 of 2009 concerning Amendments to Law Number 31 of 2004 concerning Fisheries, has provided guidance regarding sustainable management of the fisheries sector and provided criminal threats for perpetrators who destroy marine resources, but criminal acts in the field of fisheries still continue to occur in society fisherman. The purpose of this study is to provide legal solutions in increasing the prevention of fisheries crimes according to Islamic law. Islamic criminal law policy is one of the data sources in this study. The steps to be carried out are the preparation and implementation of research by collecting field data or information for analysis. The method in this study is normative juridical. Normative juridical research refers to the legal norms contained in laws and regulations as well as the existing norms in Islam. So far, fisheries crimes have been prevented in a normative way using positive law, namely the fisheries law. Prevention is carried out through supervision by the government or community groups, counseling or dissemination of rules in the field of fisheries and even to prevention through the act of punishing the perpetrators with the aim that the crime does not happen again. Fishermen as religious people will certainly comply with the rules made by the government, but in fact there are still actions that damage marine resources, even though in addition to the instructions in the rules there are also orders in the rules of Islamic law to protect and preserve the sea so that the resources contained therein can be sustainable.